EVERYONE IS TEACHER HERE LEARNING STRATEGY AS AN EFFORT TO IMPROVE STUDENT ACHIEVEMENT IN FIQIH COURSES AT MI MUHAMMADIYAH SPECIAL PROGRAM KENTENG NOGOSARI BOYOLALI - Ngatimin, N; Mujiburrohman, M; Subando, Joko (Proceeding of International Conference of Islamic Education, 2023)
The learning of everyone is a teacher here is; (a) each student has a role, (b) there is a direct interaction relationship between students, (c) each student is responsible for their learning, (d) the teacher helps develop students' interpersonal skills, (e) the teacher only interacts with students when needed. The three central concepts that characterize the learning of everyone is a teacher here are opinion appreciation, individual accountability, and equal opportunity to succeed. Learning achievement is a measure of success in learning. Learning achievement can be used as one of the considerations whether a person plunges into the world of work or continues higher education. This type of research is classroom action research which focuses on efforts to change the existing real conditions towards the expected conditions. This study uses a series of four activities carried out in repeated cycles. There are four main activities in each cycle, namely (a) planning, (b) action, (c) observation, and (d) reflection. The method of collecting data in this action research is by means of tests, questionnaires, observation and documentation. Data were analyzed with collaborating partners from the time the research was initiated, then developed during the reflection process to the report preparation process. The results in cycle I showed an increase in student learning outcomes from 49.16% to 77.31% and student achievement increased from 40.60% to 84.38%, while in cycle II showed student learning outcomes increased 3.69% from cycle I and student achievement increased 9.37% from cycle I. This shows that the learning strategy everyone is a teacher here can improve student achievement.